Internal cyclopexy for complicated traumatic cyclodialysis cleft - Wang, Cong; Jonas, Jost B. (Acta ophthalmologica, 2017)
Purpose: To assess the surgical and functional outcome of internal direct cyclopexy as therapy of complicated traumatic cyclodialysis. Methods The single-centre interventional case-series study included eyes with traumatic cyclodialysis who had consecutively been treated. Internal cyclopexy was performed using double-armed sutures introduced into the eye through the pars plana opposite to the cyclodialysis cleft and which were laid parallel to limbus. Additional procedures included cataract surgery, and pars plana vitrectomy. The cyclodialysis was documented upon ultrasound biomicroscopy and gonioscopy. Results: The study included 44 patients (44 eyes). The cyclodialysis extended over 4.8 ± 3.2 clock hours of scleral spur circumference (range 1-12 hr, median 4 hr), involving >180° of the scleral spur circumference in 16 eyes (37%) and 360° in 3 eyes (7%). Besides cyclodialysis, additional trauma-related complications included hyphema, iridodialysis, lens dislocation, cataract, vitreous haemorrhage, retinal detachment, suprachoroidal haemorrhage and endophthalmitis. The surgery performed on average at 64 days after the trauma included a mean number of 4.6 ± 1.9 sutures (range: 2-9), with 1.2 sutures per 30° width of cyclodialysis. Mean follow-up was 32 ± 8 weeks (range: 6-51 weeks). Closure of the cyclodialysis was achieved in all 44 eyes, and intraocular pressure (IOP) increased from 8.0 ± 3.4 mmHg (range: 3 21 mmHg) to 14.4 ± 4.0 mmHg (range: 11-21 mmHg). Mean visual acuity (VA) improved from 2.3 ± 1.1 logMAR (range: 0.22-4.0) to 1.2 ± 0.8 logMAR (range 0.3-4.0 logMAR). Conclusion: In conclusion, internal direct cyclopexy is a novel and relatively little invasive surgery technique for the repair of traumatic cyclodialysis.
Gesehen am 08.10.2018